Remarks on learner autonomy and success in foreign language learning as a measure of learner resilience - Puppel, Stanisław (Glottodidactica, 2012)
In a positively-oriented foreign language pedagogy, where learner autonomy is of utmost importance, focus should be placed on learner resilience. Subsequently, the formation of a resilient learner should be regarded as one of the aims of the formal schooling system on all levels of its functioning. The advantages of the presence of the resilient learner in a properly constructed ecosystem of the school are manifold and are, generally, aimed at generating a high degree of success in school tasks as well as at providing the human society with resilient participants.